Atypical hemolytic-uremic-syndrome in infants with genetic mutations. Report of three cases - Loza, Reyner (2022)
The atypical hemolytic uremic syndrome (aHUS) is a rare clinical entity, but it is the most common cause of acute kidney failure in kids. The disease is characterized by microangiopathic hemolytic anemia, thrombocytopenia and acute renal failure, and it is associated with high morbidity and systemic involvement. We report here three cases of aHUS in infants presenting with prodromal respiratory symptoms, diarrhea, hemolytic anemia, thrombocytopenia and acute renal failure. aHUS cases depict mutations in several genes: membrane cofactor protein (MCP) and complement factor H related proteins 1 and 5 (CFH, RP1 and PR5. Two our patients showed mutations in the genes CFH and MCP, and one presented a new non-previously reported mutation in the gen C3. Our results emphasize the existence of these aHUS mutations and underscore the need to study them to prevent morbidity and mortality.